Detection of Maillard reaction products by a coupled HPLC-Fraction collector technique and FTIR characterization of Cu(II)-complexation with the isolated species - Ioannou, Aristos; Daskalakis, Vangelis; Varotsis, Constantinos (My University, 2017)
The isolation of reaction products of asparagine with reducing sugars at alkaline pH and high temperature has been probed by a combination of high performance liquid chromatography (HPLC) coupled with a Fraction Collector. The UV–vis and FTIR spectra of the isolated Maillard reaction products showed structure-sensitive changes as depicted by deamination events and formation of asparagine-saccharide conjugates. The initial reaction species of the Asn-Gluc reaction were also characterized by Density Functional Theory (DFT) methods. Evidence for Cu (II) metal ion complexation with the Maillard reaction products is supported by UV–vis and FTIR spectroscopy.
Keywords: Asparagine; ATR-FTIR; Fraction collector; HPLC; Maillard reaction; UV–vis